Ecoscapes: Geographical Patternings of Relations - Aimar Ventsel (Journal of Ethnology and Folkloristics)
Book review of the publication Ecoscapes: Geographical Patternings of Relations. Edited by Gary Backhaus and John Murungi. Lanham, Boulder, New York, Toronto, Oxford, Lexington Books, 2006, xxxiii+241 pp.